Внутривидовая изменчивость и систематика каменки черной — Oenanthe picata (Вlуth) - Лоскот, В.М. (Вестник зоологии, 1972)
A study of variability in colour, sizes and some ecological characters of Oenanthe picata (B I y t h) showed a rather distinct isolation of three groups of populations, each of them having a specific morphical composition, peculiar inhabiting conditions and definite area of distribution. These populations are given the status of independent subspecies.